Combined functional genomics and genetic approach in oyster to identify summer mortality-resistant markers - Huvet, Arnaud; Lapegue, Sylvie (Marine Genomics Europe, 2008)
The oyster Crassostrea gigas has global distribution and for the past several years the highest annual production of any freshwater or marine organism. Economic importance of oysters motivates a great deal of biological research, which provides the most immediate scientific rationales for sequencing ESTs and developing genomic tools.